Inhibition of the pulmonary inactivation of prostaglandins in vivo by di-4-phloretin phosphate. - Crutchley, D J (1975)
1 Inactivation of prostaglandin E2 in the pulmonary circulation of rabbits in vivo was measured by comparing the hypotensive effects of doses given intravenously and intra-arterially. 2 Di-4-phloretin phosphate (DPP) 25-100 mug kg-1 min-1 inhibited the inactivation of prostaglandin E2 in the pulmonary circulation. 3 These doses of DPP caused a marked shift to the left of the dose-response curve to prostaglandin E2 given intravenously but did not affect the dose-response curve to prostaglandin E2 given intra-arterially. 4 Inhibition of pulmonary inactivation of prostaglandins E2 and F2alpha caused marked potentiation of their gastrointestinal effects. 5 At these doses antagonism of the hypotensive action of prostaglandin E2 by DPP was seldom seen but the gastrointestinal effect of prostaglandin F2alpha was sometimes antagonized. 6 After treatment with DPP 100 mug kg-1 min-1, high doses of prostaglandin were sometimes lethal.